Atg7-dependent autophagy promotes neuronal health, stress tolerance, and longevity but is dispensable for metamorphosis in Drosophila. - Juhász, G.; Erdi, B.; Sass, M.; Neufeld, T.P. (Genes & Development, 2007)
Autophagy, a cellular process of cytoplasmic degradation and recycling, is induced in Drosophila larval tissues during metamorphosis, potentially contributing to their destruction or reorganization. Unexpectedly, we find that flies lacking the core autophagy regulator Atg7 are viable, despite severe defects in autophagy. Although metamorphic cell death is perturbed in Atg7 mutants, the larval-adult midgut transition proceeds normally, with extended pupal development compensating for reduced autophagy. Atg7-/- adults are short-lived, hypersensitive to nutrient and oxidative stress, and accumulate ubiquitin-positive aggregates in degenerating neurons. Thus, normal levels of autophagy are crucial for stress survival and continuous cellular renewal, but not metamorphosis.